2016
DOI: 10.18844/gjflt.v6i4.1674
|View full text |Cite
|
Sign up to set email alerts
|

Wiki effect on English as a foreign language writing achievement

Abstract: The number of the studies conducted on the use of wikis on the English as a foreign language (EFL) learning process has remained fairly limited. More specifically, in the Turkish EFL context, little attention has been paid to the effects of wikis on EFL writing achievement. Thus, this study aims to examine the effects of a wiki-based writing environment in terms of EFL writing achievement in the Turkish EFL context. In this experimental study, a background questionnaire, a writing achievement pre- and a post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The researchers discovered that process writing combined with the collaborative method was effective for improving students’ writing skills and boosting their engagement in prior studies (Celik & Aydin, 2016; Li & Zhu, 2017; Li, 2020; Wang, 2015). This study’s findings are consistent with earlier research, which found that wiki collaborative process writing increased students’ writing success in areas such as content and organization (Aydin & Yildiz, 2014; Wang, 2015), grammar, vocabulary, and mechanics (Aydin & Yildiz, 2014; Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers discovered that process writing combined with the collaborative method was effective for improving students’ writing skills and boosting their engagement in prior studies (Celik & Aydin, 2016; Li & Zhu, 2017; Li, 2020; Wang, 2015). This study’s findings are consistent with earlier research, which found that wiki collaborative process writing increased students’ writing success in areas such as content and organization (Aydin & Yildiz, 2014; Wang, 2015), grammar, vocabulary, and mechanics (Aydin & Yildiz, 2014; Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Wikis, one of the computer-mediated tools created by Cunningham, aim to supply a fast software platform where users have a chance to easily and freely modify content by creating, editing, uploading, and building web content (Celik & Aydin, 2016). Some scholars have integrated both process writing and collaborative writing with wiki technology for EFL/ESL learners (Chao & Lo, 2011; Hsu, 2019; Hsu & Lo, 2018; Lee, 2010; Li & Zhu, 2017; Vurdien, 2017; Wang, 2015; Wang et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, they have no effect on cultural awareness. Çelik and Aydin (2016) experimentally examined the effects of wiki-based writing environment on writing achievement of 42 Turkish EFL learners. Background questionnaire, a writing achievement pre-and a post-test were administered.…”
Section: Using Wikis In Language Instructionmentioning
confidence: 99%
“…En el contexto ecuatoriano, escribir en inglés como lengua extranjera constituye una preocupación primordial para los estudiantes universitarios quienes necesitan esta habilidad en su vida académica porque es parte de los requisitos en cualquier carrera universitaria y les permite tener acceso a estudios de postgrado u otras oportunidades. Evidentemente, la habilidad de escribir en inglés con precisión es un aspecto esencial en términos de éxito en todos los niveles de educación y contexto profesional; por lo tanto, avanzar en la escritura de inglés como lengua extranjera brinda innumerables oportunidades y juega un papel crucial en el aprendizaje de este idioma (Celik y Aydin, 2016).…”
Section: La Escritura En La Enseñanza De Inglés Como Lengua Extranjeraunclassified